AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL BATANG Phytocrene macrophylla BLUME - Herwin, Herwin; Mile, Firna Anggriani (Jurnal Ilmiah As-Syifaa, 2017)
Antibacterial activity test has been done on Phytocrenemacrophylla Blume stem ethanol extracts. The aim of the research was to determine the antibacterial activity ofÂ  Phytocrenemacrophylla Blume Stem Ethanol extracts delivered from Gowa District of South Sulawesi by means of Agar Diffusion. The results of the screening antibacterial activity of ethanol extracts of stem Phytocrenemacrophylla Blume possessed activity against Escherichia coli, Streptococcus mutans, and Pseudomonas aeroginosa. At the minimum inhibitory concentration tests used the concentrations of 0,2%, 0,4%, 0,6%, 0,8%, 1%, 5%, 10%, and 15% of the bacteria Streptococcus mutans, Pseudomonas aeroginosa, and Escherichia coli can inhibit 0,2%. At the minimum kill concentration test against the bacteria Streptococcus mutans and Pseudomonas aeroginosa inhibited at the concentration of 0,8% and the bacteria Escherichia coli at the concentration of 1%. The test results of antibacterial activity of ethanol extract of stem Phytocrenemacrophylla Blume at the concentrations of 0.8%, 1%, and 5% inhibited the growth of bacteria. The biggest inhibitory zone of the test conducted, that is, at the concentration of 5% by 16 mm against to the bacteria Pseudomonas aeroginosa and Streptococcus mutans, and 14 mm to Escherichia coli.